Cerebral microbleeds in dementia with Lewy bodies. (November 2022) - Chin, Kai Sin; Hijazi, Zina; Churilov, Leonid; Gajamange, Sanuji; Desmond, Patricia M.; Villemagne, Victor; Rowe, Christopher; Yassi, Nawaf; Watson, Rosie
Abstract: Introduction: Cerebral microbleeds (CMB) are associated with cognitive impairment and hypertensive or cerebral amyloid angiopathy. The pathophysiology and clinical significance of CMB in dementia with Lewy bodies (DLB) are not well understood. Our study aimed to investigate the prevalence of CMB in DLB and to estimate the magnitudes of their clinical associations. Methods: Twenty participants with DLB (mean age 74 ± 5 years) were included in this cross-sectional study. All participants underwent 3 T magnetic resonance imaging. CMB number and location were assessed on susceptibility-weighted imaging or quantitative susceptibility mapping. Amyloid-beta (Aβ) positron emission tomography (PET) scans were also performed. Between-group comparisons were estimated using risk ratios (RR) for categorical variables, and mean differences or median regression coefficients for continuous variables. Results: CMB were present in 30% of the DLB participants, with a lobar predominance observed. DLB with CMB were more likely to be on antithrombotic therapy (100%), compared to those without CMB (43%; RR 2.33 [95% CI 1.27, 4.27]). Those with CMB were also more likely to report a history of hypertension (100%) compared to those without (70%; RR 1.75 [95% CI 1.11, 2.75]). DLB core clinical features, cognition and functional status did not differ between the two groups. There was no association found between the presence of CMB and cortical Aβ deposition on PET imaging. Conclusion: CMB are not uncommon in DLB and may be associated with hypertensive small vessel disease. Further studies into the pathophysiology and clinical implications of CMB in DLB are needed. Highlights: Cerebral microbleeds (CMB) were present in 30% of dementia with Lewy bodies (DLB). CMB were not associated with clinical features in DLB. CMB in DLB were associated with hypertension, but not amyloid-beta deposition.